Patient Satisfaction with Pulmonary Tuberculosis Treatment Services at Community Health Centers: An Exploratory Study - Latif, Aulia Insani; Sjattar, Elly Lilianty; Fadilah, Nur (Jurnal Keperawatan Florence Nightingale, 2025)
Tuberculosis (TB) remains a major health problem in Indonesia, with Makassar City reporting the highest number of cases in South Sulawesi. This study aimed to assess the patient satisfaction with TB treatment services. A descriptive quantitative approach was used, involving 60 patients with TB selected through purposive sampling. Data were collected using a modified QUOTE TB Light questionnaire. Most patients were male, adult, Muslim, Makassarese, and high school graduates. Key areas of dissatisfaction included limited operating hours (QI=1.41), lack of staff communication (QI=1.00), inadequate TB-HIV relationship (QI = 4.65), HIV prevention (QI = 4.73), HIV testing (QI = 4.33), inadequate provision of drinking water (QI = 1.75) and usable toilets (QI = 1.66), poor monitoring of sputum examination and treatment (QI=6.67), and lack of transportation (QI=6.19), food (QI=6.08), and financial support (QI=6.19). The findings suggest that improvements in communication, service access, infrastructure, and socioeconomic support are needed to improve patient satisfaction and treatment outcomes.